Empowering Students’ Creativity and Critical Thinking through Discovery Learning-based Writing Assessment - Kusumawardhani, Anisa Dian; Mulya, Debby; Faizah, Annisa (Linguists : Journal of Linguistics and Language Teaching, 2019)
It goes by saying that 2013 Curriculum emphasizes on the active learning and stimulates students’ high order thinking skill. Furthermore, discovery learning is one of the learning approaches which is proposed by the government to support and to construct students’ creative and critical thinking. Due to the fact that teachers’ awareness and experience in developing the learning materials and performing the discovery learning activities which encourage students to think critically and creatively is still less, this paper presents information and guidance how to construct the discovery learning-based activities which promotes high order thinking skills. Moreover, this paper limits its focus on the writing skill assessment in the senior high school. The research and development methodology was adopted in this paper. An example of simple learning activities of discovery learning-based writing assessment is provided as well. The proposed discovery learning activities cover the activities which might be done from the beginning to the end of the learning process, that is assessed in writing skill. The guidance and learning activities sample help English teachers of senior high school elaborating the discovery learning based writing assessment activities.